BAM15 as a mitochondrial uncoupler: a promising therapeutic agent for diverse diseases - Xiong, Guoji; Zhang, Kexin; Ma, Yujie; Song, Yixin; Zhang, Wenqiang; Qi, Tongbing; Qiu, Hongyan; Shi, Junfeng; Kan, Chengxia; Zhang, Jingwen; Sun, Xiaodong (Frontiers in Endocrinology, 2023)
Subcellular organelles dysfunction is implicated in various diseases, including metabolic diseases, neurodegenerative diseases, cancer, and cardiovascular diseases. BAM15, a selective mitochondrial uncoupler, has emerged as a promising therapeutic agent due to its ability to enhance mitochondrial respiration and metabolic flexibility.By disrupting the coupling between electron transport and ATP synthesis, BAM15 dissipates the proton gradient, leading to increased mitochondrial respiration and energy expenditure. This review provides a comprehensive overview of BAM15, including its mechanism of action and potential therapeutic applications in diverse disease contexts. BAM15 has shown promise in obesity by increasing energy expenditure and reducing fat accumulation. In diabetes, it improves glycemic control and reverses insulin resistance. Additionally, BAM15 has potential in non-alcoholic fatty liver disease, sepsis, and cardiovascular diseases by mitigating oxidative stress, modulating inflammatory responses, and promoting cardioprotection. The safety profile of BAM15 is encouraging, with minimal adverse effects and remarkable tolerability. However, challenges such as its high lipophilicity and the need for alternative delivery methods need to be addressed. Further research is necessary to fully understand the therapeutic potential of BAM15 and optimize its application in clinical settings.